2017
DOI: 10.1136/bmjopen-2016-012503
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative study of primary care clinicians’ views on point-of-care testing for C-reactive protein for acute respiratory tract infections in family medicine

Abstract: ObjectiveTo explore clinicians views of the barriers and facilitators to use of C-reactive protein (CRP) point-of-care tests (POCT) in US family medicine clinics for the management of acute respiratory tract infections (ARTIs) in adults.SettingFive family medicine clinics across two US states.Participants30 clinicians including 18 physicians, 9 physician residents, 2 physician assistants and 1 nurse practitioner, took part in the study.DesignA qualitative study using a grounded theory approach to thematically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 33 publications
(35 reference statements)
4
43
0
Order By: Relevance
“…Clinicians generally have positive views about using CRP POCTs to manage LRTIs, and feel that they provide an indication of disease severity, help manage patient expectations and increase their confidence in antibiotic-prescribing decisions. 67,102,103 Previous studies have also found similar concerns about the costs and implementation of CRP POCTs in the management of LRTIs in NHS primary care services. 68 Our health economic evaluation identified reduced antibiotic costs at the initial consultation but no significant differences in the total incremental cost for all causes at 4 weeks or 6 months, or if only COPD-related health-care costs were considered in the analysis.…”
Section: Interpretation and Comparison With Other Literaturementioning
confidence: 80%
“…Clinicians generally have positive views about using CRP POCTs to manage LRTIs, and feel that they provide an indication of disease severity, help manage patient expectations and increase their confidence in antibiotic-prescribing decisions. 67,102,103 Previous studies have also found similar concerns about the costs and implementation of CRP POCTs in the management of LRTIs in NHS primary care services. 68 Our health economic evaluation identified reduced antibiotic costs at the initial consultation but no significant differences in the total incremental cost for all causes at 4 weeks or 6 months, or if only COPD-related health-care costs were considered in the analysis.…”
Section: Interpretation and Comparison With Other Literaturementioning
confidence: 80%
“…This feeling is echoed by primary care physicians, who believe that point-of-care CRP testing can be helpful in supporting decision-making when combined with clinical criteria in ARIs but that care must be taken not to rely too heavily on the test. 16 Procalcitonin (PCT), the pro-hormone of calcitonin, is an acute inflammatory marker that tends to be higher in bacterial infections compared with viral infections, fungal infections, or noninfectious inflammatory responses. 17e19 It is stable in serum with a long half-life, making it a good candidate for measurement in a clinical setting.…”
Section: Individual Biomarkers Currently In Clinical Use: Erythrocytementioning
confidence: 99%
“…11,12 Also, having an observable test result to share might reassure patients that clinicians are making appropriate treatment decisions. 13 Overprescribing can also be attributed to physicians' failure to cope with parental concern. When physicians engage in reassuring worried parents too promptly, parents can feel misunderstood and restate their worries to get the physician's attention.…”
Section: Introductionmentioning
confidence: 99%